High-performance composite phase change materials for energy conversion based on macroscopically three-dimensional structural materials. Issue 2 (19th December 2018) - Yang, Jie; Tang, Li-Sheng; Bai, Lu; Bao, Rui-Ying; Liu, Zheng-Ying; Xie, Bang-Hu; Yang, Ming-Bo; Yang, Wei
Abstract : Macroscopically three-dimensional structural materials endow composite phase change materials with enhanced comprehensive performance, including excellent shape stability, high thermal conductivity and efficient energy conversion. Abstract : Macroscopically three-dimensional (3D) structural materials with tailorable properties are ideal alternatives for the fabrication of composites. High-performance composite phase change materials (PCMs), as advanced energy storage materials, have been significantly developed in recent years owing to the progress in multifunctional 3D structural materials, including metallic foams, carbon foams, graphene aerogels and porous scaffolds. This review focuses on the role of 3D structural materials in organic solid–liquid composite PCMs and the relationships between their architectures and properties (shape stability and thermal conductivity). In addition, recent progress in energy conversion using composite PCMs is included, which provides an insight into potential applications in advanced energy conversion devices and systems. Finally, future directions and challenges in the development of high-performance organic composite PCMs are presented.